More than Family Non-Family Executives in the Family Business - Aronoff, C.; Ward, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2011)
Hiring and working with non-family managers can present challenges to the family business. However, it is essential to create an environment in which non-family managers can suceed for the good of the business and the good of the family. This book explores the processes of hiring, managing, and retaining talented outside executives.
Keywords: Organization; Planning; Small business; Management; Leadership; Entrepreneurship; Family-owned business enterprises; Organization; Small Business; Management; Business Strategy/Leadership.; Entrepreneurship; Family Business